Catalysts for Biodiesel Production: A Review - Miyuranga, K.A.V.; Thilakarathne, D.; S.P.R. Arachchige, Udara; Jayasinghe, R.A.; Weerasekara, N.A. (Asian Journal of Chemistry, 2021)
As the world population and modernization increase, energy demand increases. One of the non-sustainable energy sources is fossil fuels. However, fossil fuel consumption raises various environmental and economic issues. Most of the studies focus on sustainable energy sources, which can replace fossil fuel dependence. Biodiesel is an alternative sustainable fuel for diesel power. Biodiesel can produce through the transesterification process. Since the catalyst plays a significant role in the biodiesel yield during a defined reaction time, the addition of a catalyst can increases the reaction rate. This article is outlined the several catalysts used by multiple researchers over the years to increase biodiesel yields.